Electrolyte, metal battery, preparation method thereof, and power-using device

CN119790518APending Publication Date: 2025-04-08CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380063708.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the circulation process of existing sodium metal batteries and lithium metal batteries, due to the adverse reaction between sodium metal foil or lithium metal foil and the electrolyte, the battery cycle performance is poor, and dead sodium or dead lithium is produced at high temperatures, which affects the stability of the battery. sex and safety.

Method used

Provide an electrolyte solution including electrolyte salt, polymer and solvent. The polymer forms a film layer under heating conditions to protect the metal layer, reduce the contact between the metal and the solvent, prevent the migration of metal clusters, and avoid the generation of dead sodium or dead lithium. , improve the cycle performance of the battery.

Benefits of technology

Through the formation of the polymer film layer, the cycle performance and stability of the metal battery are significantly improved, the chemical hydrogen production at high temperatures is reduced, and the safety and cycle performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790518A_ABST
    Figure CN119790518A_ABST
Patent Text Reader

Abstract

The present application relates to an electrolyte, a metal battery, a preparation method thereof and an electrical device, wherein the electrolyte comprises an electrolyte salt, a polymer and a solvent, the electrolyte salt is dissolved in the solvent, the polymer is dispersed in the solvent, and the electrolyte is a colloidal solution.
Need to check novelty before this filing date? Find Prior Art

Description

Electrolyte, metal battery, preparation method thereof, and electrical device Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an electrolyte, a metal battery, a preparation method thereof, and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect.

[0003] Currently commonly used secondary batteries, such as sodium metal batteries and lithium metal batteries, use sodium metal foil and lithium metal foil to replace negative electrode active materials such as graphite compared to sodium ion batteries and lithium ion batteries, which can achieve higher energy density. However, due to adverse reactions between sodium metal foil and lithium metal foil and electrolytes, the battery cycle performance is poor.

[0004] Summary of the Invention

[0005] In view of the technical problems existing in the background technology, the present application provides an electrolyte, aiming to improve the cycle performance of the metal battery using the electrolyte.

[0006] To achieve the above-mentioned objectives, the first aspect of the present application provides an electrolyte solution comprising an electrolyte salt, a polymer and a solvent, wherein the electrolyte salt is dissolved in the solvent, the polymer is dispersed in the solvent, and the electrolyte solution is a colloidal solution.

[0007] Compared with the prior art, this application has at least the following beneficial effects:

[0008] Without wishing to be limited to any theory, the above-mentioned electrolyte of the present application can be applied to metal batteries. After the electrolyte is injected, under curing conditions such as heating, the polymer therein easily adheres to the surface of the negative electrode in the metal battery to form a polymer film layer, thereby protecting the metal layer in the negative electrode; and the remaining components in the electrolyte can continue to play the role of the electrolyte. At the same time, due to the long chain segments of the polymer itself and the cross-linking effect between the chains, the physical barrier of the polymer film layer formed on the surface of the metal layer can reduce the contact and chemical reaction of the metal layer such as sodium metal with the solvent, and to a certain extent hinder the migration of metal clusters formed during the cycle to the isolation membrane outside the polymer film layer, avoiding the generation of dead sodium or dead lithium, thereby reducing chemical hydrogen production. In this way, the metal battery using the above-mentioned electrolyte has higher cycle performance.

[0009] In any embodiment of the present application, the electrolyte satisfies at least one of the following conditions (1-a) to (1-c):

[0010] (1-a) the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(0.2-10), and can be optionally 100:(0.5-10);

[0011] (1-b) The weight average molecular weight of the polymer is 50,000 to 2,000,000; optionally 50,000 to 1,000,000; more preferably 50,000 to 500,000;

[0012] (1-c) The polymer is an ion-conducting but electron-nonconducting polymer.

[0013] In any embodiment of the present application, the weight average molecular weight of the polymer is between 50,000 and 500,000, and the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(1-10); optionally 100:(2-7.5); or,

[0014] The weight average molecular weight of the polymer is greater than 500,000 and less than 1,000,000, and the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(0.2-5).

[0015] In any embodiment of the present application, the electrolyte satisfies at least one of the following conditions (2-a) to (2-c):

[0016] (2-a) the mass content of the electrolyte salt in the total amount of the electrolyte salt and the solvent is 5% to 25%;

[0017] (2-b) the mass content of the solvent in the total amount of the electrolyte salt and the solvent is 75% to 95%;

[0018] (2-c) The electrolyte is a non-aqueous electrolyte, and its water content is less than 100 ppm; optionally, the water content is less than 40 ppm.

[0019] In any embodiment of the present application, the electrolyte satisfies at least one of the following conditions (3-a) to (3-b):

[0020] (3-a) the polymer comprises at least one of polyether, polyester and cellulose;

[0021] (3-b) The solvent includes at least one of an ether solvent, an ester solvent, and a sulfone solvent.

[0022] In any embodiment of the present application, the electrolyte satisfies at least one of the following conditions (4-a) to (4-f):

[0023] (4-a) the polyether comprises at least one of polyethylene oxide, polypropylene oxide, ethylene oxide-propylene oxide copolymer and polyphenylene ether;

[0024] (4-b) the polyester comprises at least one of polycarboxylate and polyurethane; alternatively, the polycarboxylate comprises at least one of polycarbonate and polyacrylate; alternatively, the polyurethane comprises polyurethane;

[0025] (4-c) the cellulose comprises at least one of cellulose ether, methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose;

[0026] (4-d) the ether solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and 1,3-dioxolane;

[0027] (4-e) the ester solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, γ-butyrolactone, 1,3-propane sultone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate and ethyl butyrate;

[0028] (4-f) The sulfone solvent includes dimethyl sulfoxide.

[0029] In any embodiment of the present application, the polymer includes at least one of polyether and cellulose, and the solvent includes an ether solvent; and / or,

[0030] The polymer comprises a polyester, and the solvent comprises an ester solvent.

[0031] In any embodiment of the present application, the electrolyte salt includes at least one of a sodium salt, a lithium salt, and a potassium salt.

[0032] The second aspect of the present application provides a metal battery, which uses an electrolyte as described in any one of the above items, and the negative electrode of the metal battery includes a metal layer and a polymer film layer formed on the surface of the metal layer, and the polymer film layer includes the polymer derived from the electrolyte.

[0033] In any embodiment of the present application, the thickness of the polymer film layer is less than 1 μm; optionally, the thickness of the polymer film layer is 0.2 μm to 1 μm.

[0034] The second aspect of the present application provides a metal battery, whose negative electrode plate includes a metal layer and a polymer film layer formed on the surface of the metal layer, and the thickness of the polymer film layer is less than 1 μm; optionally, the thickness of the polymer film layer is 0.2 μm to 1 μm.

[0035] In any embodiment of the present application, the metal layer is a metal layer formed of at least one element selected from the group consisting of sodium, lithium, and potassium.

[0036] In any embodiment of the present application, the negative electrode plate further includes a negative electrode current collector and a conductive coating, the conductive coating is provided on the surface of the negative electrode current collector, and the metal layer is formed on the surface of the conductive coating away from the negative electrode current collector.

[0037] In any embodiment of the present application, the material of the conductive coating includes carbon nanotubes.

[0038] In any embodiment of the present application, the surface density of the conductive coating is 5g / m 2 ~50g / m 2 .

[0039] In any embodiment of the present application, the metal battery further includes a SEI film, and the SEI film is located between the metal layer and the polymer film layer.

[0040] The third aspect of the present application provides a method for preparing the metal battery provided in the second aspect of the present application, comprising the following steps:

[0041] Assembling the negative electrode current collector and the positive electrode sheet to obtain a battery cell;

[0042] The electrolyte provided in the first aspect of the present application is injected into the battery core, and heated and solidified to obtain the metal battery.

[0043] In any embodiment of the present application, the conditions for heat curing include: curing at a temperature of 50° C. to 70° C. for 4 hours to 24 hours; optionally, curing at a temperature of 50° C. to 60° C. for 8 hours to 15 hours.

[0044] The fourth aspect of the present application provides an electrical device, comprising the metal battery provided in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0046] FIG1 is a schematic diagram of a metal battery according to one embodiment of the present application;

[0047] FIG2 is an exploded view of the metal battery according to one embodiment of the present application shown in FIG1 ;

[0048] FIG3 is a schematic diagram of an electrical device using a metal battery as a power source according to an embodiment of the present application;

[0049] FIG4 is a scanning electron microscope image of the negative electrode surface obtained by disassembling a metal battery that has been injected and solidified but not formed in Comparative Example 1 of the present application;

[0050] FIG5 is a scanning electron microscope image of the negative electrode surface obtained by disassembling a metal battery that has been injected and solidified but not formed in Example 1 of the present application;

[0051] FIG6 is a scanning electron microscope image of a cross section of a bare copper current collector used in Example 1 of the present application;

[0052] FIG7 is a scanning electron microscope image of a cross section of a negative electrode obtained by disassembling a metal battery that has been solidified but not formed after injection according to Example 1 of the present application;

[0053] FIG8 is a scanning electron microscope image of a cross-section of the negative electrode obtained by disassembling a metal battery that has been solidified but not formed after injection according to Example 4 of the present application; FIG9 is a scanning electron microscope image of a cross-section of the negative electrode obtained by disassembling a metal battery that has been solidified according to Example 1 of the present application;

[0054] FIG10 is an electron image of the negative electrode cross section shown in FIG9 obtained by element labeling.

[0055] Explanation of reference numerals: 1. Metal battery; 11. Shell; 12. Electrode assembly; 13. Cover plate; 2. Electric device; 121. Bottom layer of negative electrode sheet; 122. First intermediate layer; 123. Second intermediate layer; 124. Top layer. DETAILED DESCRIPTION

[0056] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0057] For the sake of brevity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit; or it may be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.

[0058] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and “a variety” in “one or more” means two or more.

[0059] In the description herein, unless otherwise stated, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). Unless otherwise stated, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise stated, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0060] secondary batteries

[0061] A secondary battery is a battery that can be recharged to activate the active materials after discharge and continue to be used.

[0062] Typically, a secondary battery consists of a positive electrode, a negative electrode, and an electrolyte. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. Furthermore, a secondary battery also includes a separator, which is placed between the positive and negative electrodes to isolate them. The electrolyte conducts ions between the positive and negative electrodes.

[0063] Metal batteries

[0064] Metal batteries are a type of secondary battery. They include but are not limited to sodium metal batteries, lithium metal batteries, and potassium metal batteries.

[0065] Taking sodium metal batteries as an example, the main difference between them and sodium-ion batteries lies in the negative electrode material. Specifically, the negative electrode of a sodium metal battery contains a sodium metal layer. For example, the negative electrode can be a sodium metal electrode, or the negative electrode can be formed by depositing a sodium metal layer on a current collector such as copper foil or aluminum foil.

[0066] Research has found that, taking sodium metal batteries among metal batteries as an example, under high temperature conditions, the solubility of SEI (solid electrolyte interface) on the surface of sodium metal increases, resulting in serious side reactions when sodium metal comes into direct contact with the electrolyte, and thus causing the loss of active sodium; at the same time, when circulating or stored for a long time at high temperature, the amount of hydrogen produced by side reactions will increase sharply, which will seriously affect the battery's cycle performance and stability after collision.

[0067] electrolyte

[0068] One embodiment of the present application provides an electrolyte solution comprising an electrolyte salt, a polymer, and a solvent. The electrolyte salt is dissolved in the solvent, the polymer is dispersed in the solvent, and the electrolyte solution is a colloidal solution.

[0069] The polymer swells in the solvent, forming a colloidal solution in the electrolyte. The physical properties of the polymer in the electrolyte are significantly affected by temperature, and it readily solidifies from the electrolyte solvent under heat. Therefore, after injection into the battery, it can be cured by heating or other methods to form a polymer film.

[0070] It is understandable that the polymer and the solvent have similar functional groups and are similarly soluble in each other, so swelling can occur.

[0071] Without wishing to be limited to any theory, the above-mentioned electrolyte of the present application can be applied to metal batteries. After the electrolyte is injected, under curing conditions such as heating, the polymer therein easily adheres to the surface of the negative electrode in the metal battery to form a polymer film layer, thereby protecting the metal layer in the negative electrode; and the remaining components in the electrolyte can continue to play the role of the electrolyte. At the same time, due to the long chain segments of the polymer itself and the cross-linking effect between the chains, the physical barrier of the polymer film layer formed on the surface of the metal layer can reduce the contact and chemical reaction of the metal layer such as sodium metal with the solvent, and to a certain extent hinder the migration of metal clusters formed during the cycle to the isolation membrane outside the polymer film layer, avoiding the generation of dead sodium or dead lithium, thereby reducing chemical hydrogen production. In this way, the metal battery using the above-mentioned electrolyte has higher cycle performance.

[0072] In addition, the application of the above-mentioned electrolyte in metal batteries can also reduce the amount of hydrogen produced when the battery is circulated or stored for a long time at high temperature, thereby improving the battery cycle performance while also improving the stability of the battery after a collision.

[0073] It can be understood that since the above electrolyte is a colloidal solution, it is in a solution state and can be injected into the battery by injection, which is simple and convenient.

[0074] In some embodiments, the polymer in the electrolyte is an ion-conducting but electron-nonconducting polymer, and the polymer film formed by the polymer is an ion-conducting but electron-nonconducting film having channels for solvent and ion transmission.

[0075] In some embodiments, the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(0.2-10).

[0076] In some embodiments, the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer can be 100:0.2, 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, or 100:10; or can be 100:(0.5-10), or a range consisting of any two of the above values. Furthermore, the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer can be 100:(1-10), 100:(1-5), 100:(2-4), 100:(1-4), or 100:(4-7.5).

[0077] In some embodiments, the weight average molecular weight of the polymer is between 50,000 and 2,000,000. Optionally, the weight average molecular weight of the polymer is between 50,000 and 1,000,000, or between 50,000 and 500,000, or between 500,000 and 1,000,000.

[0078] The ratio of the combined mass of the electrolyte salt and solvent to the mass of the polymer affects the thickness of the polymer film layer. The polymer within the aforementioned weight-average molecular weight range and / or mass ratio range, together with the solvent and electrolyte salt, forms a colloidal electrolyte solution. This electrolyte, after solidification by heating or other means, forms a polymer film layer on the surface of the negative electrode current collector. This polymer film layer exhibits high stability, effectively inhibiting chemical reactions between active metals such as sodium metal and the electrolyte, thereby improving the battery's cycling performance.

[0079] In addition, the weight-average molecular weight and content of the polymer affect the viscosity and ionic conductivity of the electrolyte; the weight-average molecular weight and content of the polymer are controlled to ensure that the electrolyte maintains appropriate viscosity and excellent ionic conductivity.

[0080] Furthermore, the weight average molecular weight of the polymer is between 50,000 and 500,000, and the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(1-10); optionally 100:(2-7.5).

[0081] Furthermore, the weight average molecular weight of the polymer is greater than 500,000 and less than 1,000,000, and the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(0.2-5).

[0082] In some embodiments, the polymer includes at least one of polyether, polyester and cellulose.

[0083] As an example, the polyether may include at least one of polyethylene oxide (PEO), polypropylene oxide, ethylene oxide-propylene oxide copolymer (EOPO), and polyphenylene oxide (PPO).

[0084] Optionally, the weight average molecular weight Mw of polyethylene oxide (PEO) may be 50,000 to 500,000.

[0085] As an example, the polyester may include at least one of polycarboxylate and polyurethane.

[0086] Optionally, the polycarboxylate includes but is not limited to at least one of polycarbonate and polyacrylate.

[0087] Alternatively, polyurethane includes but is not limited to polyurethane.

[0088] Optionally, the cellulose includes but is not limited to at least one of cellulose ether, methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose (CMC).

[0089] In some embodiments, the mass content of the electrolyte salt in the total amount of the electrolyte salt and the solvent is 5% to 25%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%; it can be optionally 10% to 25%, or a selection range consisting of any two of the above point values.

[0090] In some embodiments, the mass content of the solvent in the total amount of the electrolyte salt and the solvent is 75% to 95%, for example, 75%, 80%, 85%, 90%, 95%, optionally 75% to 90%, or a selection range consisting of any two of the above point values.

[0091] In some embodiments, the electrolyte is a non-aqueous electrolyte with a water content of less than 100 ppm, optionally less than 40 ppm. Excessive water content can impair the polymer's dispersion in the solvent, leading to an uneven electrolyte state. Furthermore, water molecules can undergo reduction reactions on the negative electrode surface before sodium ions, resulting in lower first-cycle coulombic efficiency. Furthermore, water molecules can react with sodium metal, causing irreversible capacity loss. Controlling the water content of the electrolyte in this manner is beneficial for controlling battery capacity performance.

[0092] In some embodiments, the solvent includes at least one of an ether solvent, an ester solvent, and a sulfone solvent.

[0093] As an example, the ether solvent may include at least one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (TRGDME), tetraethylene glycol dimethyl ether (TEGDME), and 1,3-dioxolane (DOL);

[0094] As an example, the ester solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), γ-butyrolactone (BL), 1,3-propane sultone (1,3-PS), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP) and ethyl butyrate (EB).

[0095] As an example, the sulfone-based solvent includes dimethyl sulfoxide (DMSO).

[0096] Furthermore, in the electrolyte, the polymer backbone structure must be consistent or similar to the type of functional groups of the solvent molecules, that is, the polymer backbone must match the functional groups of the solvent molecules. In this way, according to the principle of like dissolves like, the solvent molecules can be embedded in the polymer, and the colloidal solution formed is uniform. Because the solvent molecules and polymers have similar structures and similar dissolve each other, they have strong mutual affinity, the electrolyte properties are stable, and it has excellent independent storage performance. Specifically, under the premise of ensuring a low water content in the system, the electrolyte can be sealed and stored for 10 days or even longer before use, and the battery cycle performance is exactly the same as that of fresh electrolyte.

[0097] In some embodiments, when the polymer comprises a polyether, the solvent comprises an ether solvent; and when the polymer comprises a polyester, the solvent comprises an ester solvent.

[0098] In some embodiments, the electrolyte salt includes at least one of a sodium salt, a lithium salt, and a potassium salt. As an example, the electrolyte salt is one of a sodium salt, a lithium salt, and a potassium salt. It is understood that in other examples, the electrolyte salt may also be a combination of two or more of the sodium salt, the lithium salt, and the potassium salt.

[0099] As an example, the sodium salt in the electrolyte salt can be selected from one or more of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium hexafluoroarsenate (NaAsF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(fluorosulfonyl)imide (Na[(FSO2)2N]) or sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]).

[0100] As an example, the lithium salt in the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0101] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.

[0102] Optionally, the battery is a metal battery, comprising a negative electrode plate, which comprises a metal layer. The aforementioned electrolyte is applied to the metal battery to form a polymer film layer on the surface of the metal layer. The polymer film layer comprises a polymer derived from the aforementioned electrolyte.

[0103] The negative electrode plate of the metal battery includes a polymer film layer formed on the surface of the metal layer.

[0104] In one specific example, a negative electrode active material layer is not required on the negative electrode current collector of a metal battery. During charging, active ions such as sodium ions at the electrolyte interface near the negative electrode plate gain electrons and are reduced to a single metal such as sodium metal, forming a metal layer on the negative electrode current collector.

[0105] After the metal layer surface solidifies to form a polymer film layer, it is then subjected to chemical formation. Specifically, during the current formation process, and before the potential reaches the deposition potential of sodium, the electrolyte salt and solvent contact the electrons on the surface of the negative electrode current collector through the polymer film layer, and an electrochemical reaction occurs to form an ion-conducting but electron-non-conducting SEI film, so that the SEI film is located between the current collector and the polymer film layer. Therefore, the polymer film can prevent the electrolyte from dissolving the SEI, reducing the loss of active materials such as active sodium caused by the dissolution of the SEI; further, as the potential reaches the deposition potential of sodium or lithium, the sodium ions or lithium ions pass through the polymer film layer and the SEI film, and contact the electrons on the surface of the negative electrode current collector to deposit into metals such as sodium metal or lithium metal, and then a metal layer, SEI film and polymer film layer are sequentially stacked on the surface of the negative electrode current collector. This principle process can be confirmed in conjunction with Figures 5, 9 and 10 below. The polymer film layer and SEI film both have the property of conducting ions but not conducting electrons, and have channels for solvent and ion transmission. The polymer film layer can hinder the electrolyte from dissolving the SEI formed on the surface of the negative electrode to a certain extent, reducing the loss of active materials such as active sodium caused by SEI dissolution.

[0106] In some embodiments, the thickness of the polymer film layer is less than 1 μm; optionally, the thickness of the polymer film layer is 0.2 μm to 1 μm. As an example, the thickness of the polymer film layer is 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1 μm. The thickness of the polymer film layer formed by curing the polymer in the above-mentioned electrolyte at high temperature is controlled within the above-mentioned range, with a moderate thickness. If it is too thin, the unevenness will increase, resulting in exposed sites for sodium metal; if it is too thick, the ionic conductivity will be affected, and the polarization will increase. This can further improve the cycle performance of the battery and reduce the gas production of the battery. The thickness of the polymer film layer here refers to the average thickness of the polymer film layer.

[0107] The present application provides a metal battery, wherein the negative electrode plate includes a metal layer and a polymer film layer formed on the surface of the metal layer, wherein the polymer film layer has a thickness of less than 1 μm; optionally, the polymer film layer has a thickness of 0.2 μm to 1 μm. The composition of the polymer film layer is the same as that of the above-mentioned polymer film layer.

[0108] In some embodiments, the metal layer is a metal layer formed of at least one element selected from the group consisting of sodium, lithium, and potassium. For example, the metal layer is a sodium metal layer, a lithium metal layer, or a potassium metal layer.

[0109] In some embodiments, the negative electrode plate may include a negative electrode current collector and the metal layer formed on the negative electrode current collector. It is understood that the metal layer may be formed on at least one surface of the negative electrode current collector.

[0110] The negative electrode current collector can be a conventional metal foil or a composite current collector. A composite current collector can be formed by placing a metal material on a polymer substrate. For example, the negative electrode current collector can be copper foil, aluminum foil, or the like.

[0111] In some embodiments, during the preparation of the aforementioned metal battery, a negative electrode active material layer and a metal layer are not required to be formed on the negative electrode current collector of the metal battery. Instead, a polymer film layer is formed on the negative electrode current collector after the aforementioned electrolyte is injected and solidified. During charging, active ions such as sodium ions at the electrolyte interface near the negative electrode plate gain electrons and are reduced to a single metal such as sodium metal, forming a metal layer on the negative electrode current collector. This results in a metal layer and a polymer film layer being sequentially stacked on the same surface of the negative electrode current collector. As described above, this will not be further elaborated here.

[0112] In some embodiments, a conductive coating may be provided on at least one surface of the negative electrode current collector to effectively improve the cycle performance of the battery. In this case, the metal layer is formed on the surface of the conductive coating away from the negative electrode current collector.

[0113] In some embodiments, the conductive coating comprises carbon nanotubes, such as water-based carbon nanotubes.

[0114] In some embodiments, the conductive coating has a thickness of 700 nm to 1000 nm, for example 750 nm.

[0115] In some embodiments, the conductive coating has an area density of 5 g / m 2 ~50g / m 2 , for example 10g / m 2 The areal density is calculated using the following formula: Areal density = Conductive coating mass / Area. The conductive coating mass = the mass of the waterborne carbon nanotube (CNT) primer-the mass of the current collector. Conventional mass testing methods, such as balances, can be used for this purpose. The area can be measured using a pole piece size detection system.

[0116] In other embodiments, the negative electrode is a metal electrode formed of at least one element selected from sodium, lithium, and potassium. For example, the negative electrode is a sodium metal electrode, a lithium metal electrode, or a potassium metal electrode.

[0117] Unless otherwise specified, the above raw materials can be obtained commercially.

[0118] Positive electrode

[0119] In a secondary battery, the positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0120] The positive current collector can be a conventional metal foil or a composite current collector, where the composite current collector can be formed by disposing a metal material on a polymer substrate. As an example, the positive current collector can be an aluminum foil.

[0121] The specific type of the positive electrode active material can be an active material known in the art that can be used for the positive electrode of a secondary battery, and those skilled in the art can select according to actual needs.

[0122] As an example, the positive electrode active material can include a sodium ion active material, and the sodium ion active material can be a positive electrode active material known in the art for sodium ion batteries. As an example, the sodium ion active material can include at least one of the following materials: Prussian blue (PBA) type, with the chemical formula (NaxMA[MB(CN)6]·zH2O, where MA and MB are transition metal ions, which is a compound composed of sodium, transition metal and cyanide, such as Na4Fe2(CN)6, Na4Fe(CN)6, Na1.72MnFe2(CN)6, NaMnMn(CN)6, NaNiFe(CN)6, etc.; oxide type, with the chemical formula NaxMO2, 0 < x ≤ 1, M is a transition metal element, which is composed of transition metal oxides, and the variable valence transition metals involved mainly include vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni) and copper (Cu), among which manganese and iron with relatively rich resources are most commonly used, such as NaCrO2, NaMnO2, NaMnO2, Na 0.61 Ti 0.48 Mn 0.52 O2, Na[Fe 0.5 Co 0.5 O2, NaMnO2, Na[Ni 0.25 Fe 0.5 Mn 0.25 O2, etc.; and polyanion compound type, with the chemical formula Na x M y [(XO m )[[ID=​​​​​As an example, the positive electrode active material may include a lithium ion active material, which includes, but is not limited to, one or more of lithium transition metal oxides, olivine-structured lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their modified compounds. These materials can all be obtained through commercial channels.

[0124] In some embodiments, the modified compounds of the above materials may be doping-modified and / or surface-coated modified materials.

[0125] The positive electrode film layer may also optionally include a binder, a conductive agent and other optional additives.

[0126] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers.

[0127] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0128] Isolation film

[0129] In some embodiments, the metal battery further includes a separator. The separator in this application can be any known porous separator with good chemical and mechanical stability.

[0130] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0131] One embodiment of the present application provides a method for preparing the above-mentioned metal battery, comprising the following steps:

[0132] Step S10: Assemble the negative electrode current collector and the positive electrode plate to obtain a battery cell.

[0133] It is understandable that metal batteries can be prepared according to conventional methods in the art, for example, the positive electrode sheet, separator, and negative electrode current collector are wound or stacked in sequence, and the separator is placed between the positive electrode sheet and the negative electrode current collector to play an isolating role to obtain a battery cell.

[0134] Step S20: injecting the above electrolyte into the obtained battery cell, heating and curing it, and then forming it into the metal battery.

[0135] Specifically, the battery cell is placed in an outer package, the electrolyte is injected and sealed, heated and solidified, and then formed into a metal battery. It is understood that the electrolyte has weak fluidity, so that it can be added by injection.

[0136] In some embodiments, the formation conditions include: after standing, charging at a constant current of 0.05C-0.33C to 3.5V, and then discharging at a constant current of 0.05C-0.33C to 3.2V.

[0137] In a specific example, the formation conditions include: after standing still, charging to 3.5V at a constant current rate of 0.1C, and then discharging to 3.2V at a constant current rate of 0.1C.

[0138] In some embodiments, the heat curing conditions include curing at a temperature of 50-70°C for 4-24 hours. The heat curing temperature can be 50°C, 55°C, 60°C, 65°C, or 70°C, optionally 50-60°C, or a range consisting of any two of the above values. The heat curing time can be 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 23 hours, or 24 hours, optionally 8 hours to 15 hours, or a range consisting of any two of the above values.

[0139] In a specific example, the heat curing condition includes curing at a temperature of 55° C. for 12 hours.

[0140] The above temperature affects the physical state of the polymer and determines whether the polymer can be cured; the above time affects whether the polymer can be completely cured.

[0141] The shape of the metal battery in the embodiment of the present application can be cylindrical, square or any other shape. As shown in FIG1 , a metal battery 1 with a square structure is shown as an example.

[0142] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The above-mentioned electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the metal battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.

[0143] In addition, the present invention also provides an electrical device, which includes at least one of the metal battery, battery module, or battery pack provided by the present invention. The metal battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0144] As the electrical device, a metal battery, a battery module or a battery pack can be selected according to its usage requirements.

[0145] Fig. 3 shows an example of an electric device 2. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0146] As another example, the device may be a mobile phone, a tablet computer, a laptop computer, etc.

[0147] The beneficial effects of the present application are further illustrated below with reference to the examples.

[0148] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit this application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0149] The materials used in the examples of this application can all be obtained commercially.

[0150] 1. Battery Preparation

[0151] Example 1

[0152] 1. Preparation of electrolyte

[0153] The dehydrated ethylene glycol dimethyl ether (DME) and sodium hexafluorophosphate (NaPF6) were weighed in a total of 10g of sample in a mass ratio of 85:15, and then the weighed sample was placed in a 20mL black-capped glass bottle to dissolve the mixed solution. After it was completely dissolved, it was allowed to stand for 4 hours for use. The dehydrated polyethylene oxide (PEO) (the mass ratio of which to sodium hexafluorophosphate was 2:15) was slowly added dropwise to the above mixed solution, and mechanical disturbance was continued in an electric shaker for 4 hours. After a slightly white uniform colloidal solution was formed, it was allowed to stand for use to obtain an electrolyte. The above operations were all carried out in a glove box, and the water and oxygen contents of the glove box were controlled below 1ppm.

[0154] 2. Negative electrode

[0155] The battery system used in this test is a negative electrode-free sodium metal system. A 1wt% aqueous dispersion of carbon nanotubes was ultrasonically treated for 30 minutes and then spread onto a copper current collector with a scraper. After drying, cold pressing, and slitting, a negative electrode-free electrode was obtained. The electrode was a copper current collector coated with a water-based carbon nanotube (CNT) primer with a surface density of 10g / m 2 , with a thickness of 750nm.

[0156] 3. Positive electrode

[0157] The positive electrode active material sodium vanadium phosphate (NVP), the conductive agent carbon black Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:4:6 and evenly dispersed in N-methylpyrrolidone (NMP) to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0158] 4. Isolation film: 7μm thick polyethylene (PE) porous polymer isolation film.

[0159] 5. Laminated battery production

[0160] Cut the positive electrode sheet, negative electrode sheet and separator obtained above into appropriate sizes, stack them in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then use aluminum-plastic film of appropriate size to encapsulate the positive and negative electrodes and the separator, leaving a liquid injection port.

[0161] 6. Liquid injection and packaging

[0162] The obtained laminated battery was placed in a drying oven under vacuum at 85°C for 12 hours, and the dried battery cell was taken out. When the battery cell temperature cooled to room temperature, the above-prepared electrolyte (24 hours after preparation) was injected into the battery with an injection volume of 0.5g. After the injection was completed, the injection port was heat-sealed and allowed to stand at 55°C for 12 hours to cure. Then, a clamp was placed on the packaged battery cell, and appropriate pressure was applied to both ends of the clamp to complete the assembly of the laminated battery.

[0163] 7. Laminated battery formation

[0164] The assembled stacked battery was then subjected to formation treatment, and the specific formation steps were as follows: after standing for 2 hours, it was charged to 3.5V at a constant current rate of 0.1C, and then discharged to 3.2V at a constant current rate of 0.1C.

[0165] Example 2

[0166] The preparation steps of Example 2 are exactly the same as those of Example 1, except that the electrolyte of Example 2 is stored for several days before being used for battery filling. The details are as follows:

[0167] The resulting electrolyte was sealed and stored at 25°C for 10 days. If its fluidity decreased, it was mechanically agitated for 30 minutes on an electric shaker to restore its fluidity. The electrolyte was then allowed to stand for 1 hour before use. All of the above operations were performed in a glove box, where the water and oxygen contents were kept below 1 ppm.

[0168] Examples 3 to 13

[0169] Except that the components and proportions of the electrolyte used are the same as those in Table 1, other steps are the same as those in Example 1.

[0170] It should be noted that in Examples 3 to 5, CMC is carboxymethyl cellulose, PPO is polyphenylene ether, and EOPO is ethylene oxide-propylene oxide copolymer.

[0171] Comparative Examples 1 to 4

[0172] Except that the proportions of the components of the electrolyte used are the corresponding proportions in Table 1, the other steps are the same as those in Example 1.

[0173] 2. Colloidal test of electrolyte

[0174] The electrolytes prepared above were subjected to Tyndall test. The results showed that the electrolytes of each embodiment showed Tyndall phenomenon, while the electrolytes of each comparative example 1 to 4 did not show Tyndall phenomenon.

[0175] Comparative Example 1 did not contain any polymer and was a solution. The electrolytes of Comparative Examples 2 and 3 had polymers of relatively low molecular weight and content, completely dissolving in the solvent and exhibiting the same properties as a solution, rather than a colloidal solution. The electrolyte of Comparative Example 4 contained a relatively high content of polymer and was in a semisolid state.

[0176] 3. Battery Performance Evaluation

[0177] The performance evaluation of each battery was carried out according to the following method.

[0178] 1. Determination of the morphology of the negative electrode and the thickness of the polymer

[0179] In Example 1 and Comparative Example 1, the metal battery cells that were injected and solidified but not formed were disassembled to remove the negative electrode sheets, vacuum protected and transferred, and the surfaces of the negative electrode sheets were tested by scanning electron microscopy. The resulting scanning electron micrographs of the negative electrode surfaces are shown in Figures 4 and 5, respectively. In Figure 4, a, b, and c are scanning electron micrographs of the surface of the negative electrode sheet of Example 1 at different magnifications, and d, e, and f in Figure 5 are scanning electron micrographs of the surface of the negative electrode sheet of Comparative Example 1 at different magnifications. By comparing Figures 4 and 5, it can be clearly seen that there are differences in the surface morphology. At different magnifications in Figure 4, the electrolyte added with PEO in Example 1 is cross-linked and passivated to form a polymer film layer on the surface of the negative electrode side current collector, and there are many nano-scale ion channels, which ensure the ionic conductivity of the polymer film layer, thereby protecting the metal sodium layer deposited between the negative electrode current collector and the polymer film layer, reducing the contact between the sodium metal layer and the electrolyte, and thus suppressing the side reaction of the sodium metal and the electrolyte to a certain extent.

[0180] Scanning electron microscope images of the cross-section of the bare copper current collector used in Example 1 at different magnifications are shown in Figure 6. In Example 1 and Example 4, after liquid injection and curing but not yet formed, the metal battery cells were disassembled to remove the negative electrode pole pieces, vacuum protected and transferred, and the cross-sections of the negative electrode pole pieces were tested by scanning electron microscope. The resulting scanning electron microscope images of the negative electrode cross-section at different magnifications are shown in Figures 7 and 8, respectively. By comparison, it can be seen that in Example 1 and Example 4, before liquid injection and curing but not yet formed, a thin film is formed on the negative copper current collector, namely the polymer film layer formed by liquid injection and curing, as shown in the arrows in Figures 7 and 8.

[0181] The batteries prepared after formation in each embodiment and comparative example were used as samples, and then charged and discharged for one cycle at a current of 0.02C at 25°C. The battery cells were disassembled in an inert atmosphere glove box to remove the negative electrode sheets, vacuum-protected and transferred, and the cross-section of the negative electrode sheets was tested by scanning electron microscopy.

[0182] Scanning electron micrographs (SEM) of a cross-section of the negative electrode obtained from a disassembled metal battery after curing in Example 1, taken at different magnifications, are shown in Figure 9. It is clear from these images that the negative electrode sheet has a multi-layered structure. Further electron images of the negative electrode cross-section shown in Figure 9, obtained by elemental labeling, are shown in Figure 10. Elemental analysis reveals that the bottom layer 121 of the negative electrode sheet is primarily a Cu-distributed region, representing the copper current collector; the first intermediate layer 122 is primarily a C-distributed region, representing the carbon nanotube conductive coating; the second intermediate layer 123 is primarily a Na-distributed region, representing the metallic sodium layer; and the topmost layer 124, which is relatively dark and primarily a O-distributed region, represents a polymer film layer. Therefore, the negative electrode sheet in the battery produced in this example comprises a current collector and, in sequence, a conductive coating, a metallic sodium layer, and a polymer film layer stacked on the same surface of the current collector.

[0183] It should be noted that since the sample contains sodium metal element, which is relatively active in nature, the test sample can only be prepared in a glove box environment and cannot be sprayed with gold, so the polymer film layer with poor electron conductivity will be darker.

[0184] From the scanning electron microscope image of the negative electrode cross section obtained by disassembling the solidified metal battery, the thickness of the polymer film layer in each embodiment and comparative example can be obtained, and the results are shown in Table 1.

[0185] 2. Cycle performance test

[0186] Under a constant temperature environment of 25 ℃, the first charge and discharge were carried out, and constant current and constant voltage charging (charging to a current of 0.02C) was performed at a charging current of 0.1C (i.e., the current size for full charging or discharging to the theoretical capacity within 10 hours) until the upper limit voltage reached 3.5V. After standing for 5 minutes, constant current discharge was performed at a discharge current of 0.1C until the final voltage was 3.2V. The discharge capacity of the first cycle was recorded, and then a continuous 1C charge and discharge cycle was performed.

[0187] Capacity retention rate at the nth cycle=(discharge capacity at the nth 1C cycle / discharge capacity at the first 1C cycle)×100%.

[0188] 3. Hydrogen production test of high temperature storage

[0189] The test steps for gas production after 20 days of full charge storage at 60°C are as follows:

[0190] At 60°C, the battery was charged at a constant current of 0.1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current of ≤0.05C, and then discharged at a constant current of 0.1C to a voltage of 2.5V, and the actual discharge capacity of the battery was recorded as C0. At 25°C, the battery was continued to be charged at a constant current of 0.1C to a voltage of 3.65V, and then charged at a constant voltage of 3.65V to a current of ≤0.05C. At this time, the battery was fully charged, and the volume of the battery was measured and recorded as the volume of the battery before storage. The fully charged battery was placed in a constant temperature box at 60°C for storage. After 20 days of storage, the battery was removed from the constant temperature box and the volume was measured.

[0191] Gas generation amount (mL) of the battery when stored at 60°C for 20 days = (volume of the battery after 20 days of storage - volume of the battery before storage).

[0192] It should be noted that the amount of hydrogen produced during high-temperature storage can reflect the generation of dead sodium or lithium during prolonged cycling or storage at high temperatures. Lower hydrogen production indicates less dead sodium or lithium, reducing the risk of fire and explosion after a collision, and correspondingly improving the battery's stability after a collision.

[0193] Table 1

[0194] As described above, the electrolytes of Comparative Examples 1 to 4 did not exhibit the Tyndall phenomenon.

[0195] Comparative Example 1 does not add polymer and is a solution. The electrolytes of Comparative Examples 2 and 3 have a small molecular weight and content of the added polymer, which is completely dissolved in the solvent and has the same properties as a solution. It does not have the properties of a colloidal solution and cannot be solidified when left standing at 55°C after injection. The batteries of Comparative Examples 1 to 3 did not form a polymer film layer after the standing curing and formation steps. This is because no polymer is added to the electrolyte or the molecular weight and content of the added polymer are small, so its physical state is close to that of a pure salt solution without polymer addition, which has no optimization effect on the cycle performance.

[0196] The electrolyte of Comparative Example 4 has a large added polymer content and a large particle size. It does not have the properties of a colloidal solution and is similar to a semi-solid state. The battery can also form a polymer film layer after curing. However, the polymer film layer is too thick, which seriously reduces the ionic conductivity and increases the polarization, making it impossible to fully utilize the charge and discharge capacity, thereby seriously reducing the cycle performance of the battery.

[0197] The electrolytes in each example exhibited the Tyndall phenomenon, indicating that the electrolytes were all colloidal solutions. Compared to the comparative examples, the electrolytes in each example formed a polymer film layer after the battery was cured, which greatly improved the battery cycle performance.

[0198] Furthermore, compared with Comparative Examples 1 to 3, the batteries of each embodiment have improved cycle performance and significantly reduced gas production under high-temperature storage conditions, indicating that the electrolyte of the present application not only effectively improves the battery cycle performance, but also improves the stability of the battery after a collision.

[0199] Compared with Example 1, the performance of the electrolyte in Example 2 after storage for 10 days is comparable to that of Example 1, indicating that the electrolyte in the embodiment of the present application has excellent independent storage performance.

[0200] The above embodiments only list ether solvent systems. Other chemical systems that meet the principles of this application can also achieve the effects of this application. Based on the introduction of this application, those skilled in the art can know the implementation scheme and predict the technical effects.

[0201] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present application, and such modifications or substitutions should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.

Claims

1. An electrolyte solution comprising an electrolyte salt, a polymer and a solvent, wherein the electrolyte salt is dissolved in the solvent, the polymer is dispersed in the solvent, and the electrolyte solution is a colloidal solution.

2. The electrolyte according to claim 1, wherein The electrolyte satisfies at least one of the following conditions (1-a) to (1-c): (1-a) the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(0.2-10), and can be optionally 100:(0.5-10); (1-b) The weight average molecular weight of the polymer is 50,000 to 2,000,000; optionally 50,000 to 1,000,000; more preferably 50,000 to 500,000; (1-c) The polymer is an ion-conducting polymer that does not conduct electrons.

3. The electrolyte according to claim 1, wherein The weight average molecular weight of the polymer is between 50,000 and 500,000, and the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(1-10); or can be 100:(2-7.5); or, The weight average molecular weight of the polymer is greater than 500,000 and less than 1,000,000, and the ratio of the sum of the mass of the electrolyte salt and the solvent to the mass of the polymer is 100:(0.2-5).

4. The electrolyte according to any one of claims 1 to 3, wherein The electrolyte satisfies at least one of the following conditions (2-a) to (2-c): (2-a) the mass content of the electrolyte salt in the total amount of the electrolyte salt and the solvent is 5% to 25%; (2-b) the mass content of the solvent in the total amount of the electrolyte salt and the solvent is 75% to 95%; (2-c) The electrolyte is a non-aqueous electrolyte, and its water content is less than 100 ppm; optionally, the water content is less than 40 ppm.

5. The electrolyte according to any one of claims 1 to 4, wherein The electrolyte satisfies at least one of the following conditions (3-a) to (3-b): (3-a) the polymer comprises at least one of polyether, polyester and cellulose; (3-b) The solvent includes at least one of an ether solvent, an ester solvent and a sulfone solvent.

6. The electrolyte according to claim 5, wherein The electrolyte satisfies at least one of the following conditions (4-a) to (4-f): (4-a) the polyether comprises at least one of polyethylene oxide, polypropylene oxide, ethylene oxide-propylene oxide copolymer and polyphenylene ether; (4-b) the polyester comprises at least one of polycarboxylate and polyurethane; optionally, the polycarboxylate comprises at least one of polycarbonate and polyacrylate; optionally, the polyurethane comprises polyurethane; (4-c) the cellulose comprises at least one of cellulose ether, methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose; (4-d) the ether solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and 1,3-dioxolane; (4-e) the ester solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, γ-butyrolactone, 1,3-propane sultone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate and ethyl butyrate; (4-f) The sulfone solvent includes dimethyl sulfoxide.

7. The electrolyte according to any one of claims 1 to 6, wherein The polymer includes at least one of polyether and cellulose, and the solvent includes an ether solvent; and / or, the polymer includes polyester, and the solvent includes an ester solvent.

8. The electrolyte according to any one of claims 1 to 7, wherein The electrolyte salt includes at least one of a sodium salt, a lithium salt and a potassium salt.

9. A metal battery, wherein the electrolyte used is the electrolyte as described in any one of claims 1 to 8, the negative electrode plate of the metal battery comprises a metal layer and a polymer film layer formed on the surface of the metal layer, and the polymer film layer comprises the polymer derived from the electrolyte.

10. The metal battery according to claim 9, wherein: The thickness of the polymer film layer is less than 1 μm; optionally, the thickness of the polymer film layer is 0.2 μm to 1 μm.

11. A metal battery, wherein the negative electrode plate comprises a metal layer and a polymer film layer formed on the surface of the metal layer, wherein the thickness of the polymer film layer is less than 1 μm; optionally, the thickness of the polymer film layer is 0.2 μm to 1 μm.

12. The metal battery according to any one of claims 9 to 11, wherein: The metal layer is a metal layer formed of at least one element selected from the group consisting of sodium, lithium and potassium.

13. The metal battery according to any one of claims 9 to 12, wherein: The negative electrode plate further includes a negative electrode current collector and a conductive coating. The conductive coating is disposed on the surface of the negative electrode current collector, and the metal layer is formed on the surface of the conductive coating away from the negative electrode current collector.

14. The metal battery according to claim 13, wherein: The material of the conductive coating includes carbon nanotubes.

15. The metal battery according to any one of claims 13 to 14, wherein: The surface density of the conductive coating is 5 g / m 2 ~50g / m 2 .

16. The metal battery according to any one of claims 9 to 15, wherein: The metal battery further includes a SEI film, and the SEI film is located between the metal layer and the polymer film layer.

17. A method for preparing a metal battery, comprising the following steps: Assembling the negative electrode current collector and the positive electrode sheet to obtain a battery cell; The electrolyte according to any one of claims 1 to 8 is injected into the battery core, heated and solidified, and then chemically formed to obtain the metal battery.

18. The preparation method according to claim 17, wherein: The heating curing conditions include: curing at a temperature of 50° C. to 70° C. for 4 h to 24 h; optionally, curing at a temperature of 50° C. to 60° C. for 8 h to 15 h.

19. An electrical device, wherein: A metal battery comprising a metal battery selected from any one of claims 9 to 16.